Effectiveness of PTR Home-based Exercise and Education Program in COPD Patients: Systematic Review - Trisnowiyanto, Bambang; Arif Fadli (Universitas Muhammadiyah Surakarta, 2024)
Introduction: Pulmonary rehabilitation (PR) in chronic obstructive pulmonary disease (COPD) patients requires time and full adherence to the treatment program. The difficulty of transportation and the patient's economic barriers raise the need for pulmonary telerehabilitation (PTR). The purpose of this study was to summarize existing literature data regarding the effectiveness of PTR home-based exercise and education program in COPD Patients. Methods: A systematic review with qualitative descriptive analysis method of the study from the electronic database Pubmed, Willey Online Library, Science Direct, EBSCO, Ovid. Results: There are 6 articles included in this study that stated that the effectiveness of home-based PTR exercise and education programs is comparable to hospital-based PR exercise and education programs in evaluating exercise capacity and quality of life. 5 articles had a dropout rate from participants in the intervention group <20% and 1 article had a dropout rate from participants in the intervention group >20%. 3 articles had a dropout rate from control group participants <20% and 3 articles had a dropout rate from control group participants >20%. Conclusion: Effectiveness of the PTR home-based exercise and education program is comparable to the effectiveness of the hospital-based PR exercise and education program in evaluating exercise capacity and quality of life with the cost efficiency of treatment.